The effect of family resilience intervention program for caregivers of schizophrenia patient - Lestari, Puji; Liyanovitasari, Liyanovitasari; Prabowo, Heri (Intelektual Pustaka Media Utama, 2025)
Caregivers with schizophrenia face physical, psychological, and financial burdens. Although existing research supports the efficacy of interventions to improve the mental health and wellbeing of caregivers living with schizophrenia patients, there are a number of limitations to the existing evidence. This study aims to assess the effectiveness of a family resilience intervention program for caregivers with schizophrenia using a randomized controlled trial in Central Java, Indonesia. This is a non-blinded study with two parallel arms and an active control group. The intervention group received a combination of face-to-face and interactive online delivery strategies for six weeks. The conner–davidson resilience scale and McMasters family assessment device (FAD) were used to measure study outcomes. The study uses repeated measures analysis of variance, Cohen' d test, and general estimate equations to analyze the data. The study involved over 230 caregivers and found that the family resilience intervention program significantly improved resilience and family functioning scores after the intervention. The study also revealed a moderate effect size on resilience and family functioning. The study suggests that primary healthcare centers should be involved in early detection and monitoring of psychosocial issues within families to maintain and improve their mental health.